Preparation method of ginger paper loaded with polysaccharide nanoparticles

Through low-temperature extraction method and nanotechnology, ginger paper loaded with polysaccharide nanoparticles was constructed, which solved the problems of uneven efficacy of Chinese medicine and insufficient hygiene standards in moxibustion, and achieved effective transmission and continuous release of active ingredients in traditional Chinese medicine, which was suitable for personalized treatment. need.

CN119221319APending Publication Date: 2024-12-31GUANGZHOU BAIYIKANG BIOTECHNOLOGY DEV CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411350954.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing moxibustion products have problems of uneven heat and humidity under traditional combustion methods, and cannot effectively conduct active ingredients of traditional Chinese medicine to the skin. They lack hygiene standards and quality control, so they cannot achieve the personalized treatment effect of moxibustion for thousands of people.

Method used

Polysaccharide particles were extracted from ginger, Angelica, Atractylodes macrocephala, Poria cocos and Atractylodes macrocephala by low-temperature extraction, and a drug-loaded film was formed through corn starch, and a three-layer nanostructured ginger was constructed by combining modified kapok fibers and mica nanoparticles. paper to improve drug loading and conductivity.

Benefits of technology

It realizes the uniform transmission and absorption of active ingredients of traditional Chinese medicine, enhances the efficacy of moxibustion, ensures the continuous release and uniform effect of the drug, and improves the thermal insulation performance and hygiene standards, which is suitable for the personalized treatment needs of different groups of people.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119221319A_ABST
    Figure CN119221319A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of polysaccharide nanotechnologies, and discloses a preparation method of ginger paper loaded with polysaccharide nanoparticles, which comprises the following steps: taking hydrophilic plant fibers as a matrix, and taking mica powder modified active carrier particles with expanded micropores and positive ions as a skeleton to obtain a ginger paper fiber energy storage layer; the ginger paper with a three-layer structure including the ginger paper fiber matrix layer, the ginger paper fiber energy storage layer and the medicine carrying film loaded with the polysaccharide nano particles is prepared, active substances such as the polysaccharide nano particles in the energy storage layer pass through a micropore structure of mica, and the medicine carrying film loaded with the polysaccharide nano particles can be used for preparing the ginger paper with the three-layer structure of the ginger paper fiber matrix layer, the ginger paper fiber energy storage layer and the medicine carrying film loaded with the polysaccharide nano particles. By means of a transmission structure of the net-shaped framework, active substances in the medicine carrying film are rapidly activated, the active ingredients are absorbed by the human body, and the effects of outwards discharging moisture and cold and inwards transferring the active ingredients of traditional Chinese medicine in the moxibustion process are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polysaccharide nanoparticles, and in particular to a method for preparing ginger paper loaded with polysaccharide nanoparticles. Background Art

[0002] Moxibustion has a history of more than 5,000 years. In ancient times, moxibustion was performed by grinding Chinese medicinal materials into powder, placing them on relevant acupuncture points, and surrounding them with flour balls to prevent air leakage. Sophora bark with small holes or ginger slices were placed on top, and then moxa sticks the size of a date pit were placed on the sophora bark or ginger slices, and then ignited for moxibustion. Moxibustion, through continuous warming of acupuncture points, dredges blocked meridians and blood, invigorates low or declining functions, balances imbalanced yin and yang, eliminates pain, restores health, and delays aging. At present, the mainstream method of implementing moxibustion on the market is still the traditional direct moxibustion by burning moxa. Traditional direct moxibustion uses different Chinese medicinal materials such as ginger and garlic, and burns moxa sticks to achieve the therapeutic and health-care effects of moxibustion. Although moxibustion follows ancient methods, the choice of Chinese medicinal materials, dosage, and acupoints varies from person to person. The ancient prescriptions only use different moxibustion methods for different symptoms, and it is impossible to achieve different moxibustion methods for different people. Moreover, there are no hygiene standards in the production process of the partition, and there are no clear standards for the quality and dosage of the medicinal materials used in the partition. The light and heat of moxibustion directly act on fresh plant partitions, which easily forms a unidirectional heat and humidity channel, which is not conducive to the excretion of moisture and cold from the body during the moxibustion process.

[0003] The Chinese patent with publication number CN109837787A discloses a traditional Chinese medicine mugwort paper and its preparation process, wherein the raw materials include 30-50 parts of mugwort, 20-40 parts of ginger, 30-50 parts of kudzu root, and 20-25 parts of mulberry bark by weight; the preparation process includes the following steps: material selection, cleaning, drying, crushing, hot grinding, pulping, and papermaking. The mugwort paper in the patent has a single component, low mechanical strength, uneven heat insulation and heat transfer, and is not suitable for use as a product for moxibustion.

[0004] The Chinese patent with the publication number CN113308001B discloses a method for preparing antibacterial paper with nanoparticles, which comprises the following steps: S1, taking curcumin and hawthorn polysaccharide crude extract powders and dissolving them respectively, then adding the curcumin solution dropwise to the hawthorn polysaccharide crude extract solution, adding sodium tripolyphosphate solution after the dropwise addition and starting stirring, and then stopping the addition and sequentially performing ultrasonication, centrifugation, and freeze drying to obtain curcumin / hawthorn polysaccharide crude extract nanoparticles; S2, gelatinizing corn starch, cooling and mixing with curcumin / hawthorn polysaccharide crude extract nanoparticles, adding glycerol to the mixture and mixing evenly, casting into a film, and then drying to obtain starch antibacterial paper. Although the antibacterial paper with nanoparticles prepared by this method is also ginger paper made of ginger and polysaccharide nanoparticles, and has excellent antibacterial and antibacterial effects, it is not suitable for use as a product for moxibustion due to its surface structure.

[0005] The Chinese herbal medicine carried on the plant fiber paper can be any Chinese herbal medicine suitable for moxibustion except the ingredients of moxa sticks. During moxibustion, the Chinese herbal medicine carried on these plant fiber paper can give full play to the effect of Chinese herbal medicine fumigation. The plant fiber paper loaded with polysaccharide nanoparticles can promote the effect of moxibustion. There is no such a product at present. Therefore, a new pad technology loaded with polysaccharide nanoparticles is urgently needed to solve the problem of how to conduct the effective substances to the skin to the greatest extent during the moxibustion process, so that they can be absorbed by the human body, and can expel moisture and cold to the outside, and transfer heat to the inside to transfer the active ingredients of Chinese medicine, so as to carry forward and inherit the real traditional moxibustion. Summary of the invention

[0006] In order to solve the above problems, the purpose of the present invention is to provide a method for preparing ginger paper loaded with polysaccharide nanoparticles to solve one or more technical problems existing in the prior art and at least provide a beneficial choice or create conditions.

[0007] According to one aspect of the present invention, polysaccharide particles are first extracted from Chinese herbal medicine. In order to achieve the above purpose, a low-temperature extraction method is provided, and the extraction method comprises the following steps:

[0008] S001, clean the extract, freeze-dry it and then grind it to obtain a grinded mixture,

[0009] S002, adding an ethanol solution 2 to 4 times the weight of the mixture to the crushed mixture, placing it in an ultrasonic extractor for extraction, filtering to obtain a first-stage extract and a first-stage filter residue for standby use;

[0010] S003, concentrating the first-stage extract in step S002 under reduced pressure to a concentrated solution that is 0.1 to 0.2 times the weight of the first-stage extract to obtain a first concentrated solution;

[0011] S004, adding 2 to 4 times ethanol solution to the first-stage filter residue in step S002, placing it in an ultrasonic extractor for secondary extraction, and filtering to obtain a second-stage extract and a second-stage filter residue;

[0012] S005, concentrating the second-stage extract under reduced pressure to a concentrated solution 0.1 to 0.2 times the weight of the second-stage extract; mixing with the first concentrated solution in step S003 to obtain a second concentrated solution, and fully stirring at a temperature of 2° C. to 8° C.;

[0013] S006, taking the second concentrated solution in step S005, performing centrifugal filtration, and concentrating under reduced pressure to remove ethanol, to obtain an active substance extract. The second filter residue is dried at low temperature and then used for later use.

[0014] S007, deproteinization treatment was performed by Sevag method. Sevag reagent was added to the active substance extract at a volume ratio of 5:1, stirred for 30 to 60 minutes, and the upper polysaccharide solution was collected after standing and stratification. The organic layer and the protein layer were centrifuged, and the remaining polysaccharide solution was collected after centrifugation to obtain a deproteinized polysaccharide solution. The deproteinized polysaccharide solution was carefully transferred to a 3500Da dialysis bag for dialysis for 72 hours. After the dialysis was completed, it was concentrated under reduced pressure and freeze-dried to obtain polysaccharide particles.

[0015] S008, gelatinizing corn starch, mixing it evenly with polysaccharide particles after cooling, adding glycerol to the mixture and mixing evenly, casting it into a film, and drying it to obtain a drug-loaded film loaded with polysaccharide nanoparticles; the mass ratio of the polysaccharide particles to the corn starch is 1:5.

[0016] The Sevag reagent is a mixed solution of chloroform and n-butanol with a volume ratio of 4:1;

[0017] The ultrasonic power is 50-100W, the extraction time is 1-2h, and the mass percentage concentration of the ethanol solution is 70-80%.

[0018] The extract is a mixture of ginger, angelica, atractylodes, poria and atractylodes, wherein ginger is 30-40 parts, angelica is 5-8 parts, atractylodes is 10-15 parts, poria is 10-15 parts and atractylodes is 5-8 parts;

[0019] Furthermore, the ginger paper loaded with polysaccharide nanoparticles is a three-layer nanostructure, which includes a ginger paper fiber matrix layer, a ginger paper fiber energy storage layer, and a drug-loaded film loaded with polysaccharide nanoparticles from the outside to the inside;

[0020] The preparation method of the ginger paper fiber matrix layer is specifically as follows:

[0021] The plant fiber is cut into pieces by a high-speed shearing machine, and the plant fiber is surface treated with a 3% dilute sulfuric acid solution. Then, the plant fiber is washed with deionized water until neutral and then put into a pulper for pulping to obtain plant fiber pulp. Finally, the plant fiber pulp is put into a high-pressure homogenizer for high-pressure homogenization to prepare a cellulose solution, to which a cationic surfactant hexadecyltrimethylammonium bromide with a mass concentration of 0.2% is added to make it evenly dispersed.

[0022] The plant fiber is Chinese herbal medicine filter residue and kapok fiber, the mass fraction of kapok fiber is 20 to 30 parts, the Chinese herbal medicine filter residue is the dried second-stage filter residue, and the mass fraction of the dried second-stage filter residue is 80 to 100 parts;

[0023] The slurry is evenly mixed by stirring and the bubbles therein are discharged as much as possible, the viscosity is adjusted to 20-50cp at a temperature of 50°C, and the slurry is coated on a paper base and filtered to form a wet paper sheet. Finally, the wet paper sheet is placed in a flat dryer set at a temperature of 100°C and dried to a constant weight to obtain a ginger paper fiber matrix layer.

[0024] We found that the ginger paper fiber matrix layer obtained by such treatment is relatively loose, porous, and highly hydrophobic due to the presence of kapok fibers, and is not easy to absorb moisture; and the lipophilicity of kapok fibers makes the ginger paper matrix obtained after film formation with cellulose solution show uneven dispersion of kapok fibers, resulting in uneven drug loading, poor transferability and conductivity in subsequent use, which in turn leads to poor effect of inward heat transfer of the active ingredients of traditional Chinese medicine.

[0025] In order to improve the drug loading capacity, conductivity and uniform and effective drug delivery of the ginger paper matrix, firstly, the kapok fiber was hydrophilically modified as follows:

[0026] S101, boiling the kapok fiber in a 3% dilute sulfuric acid solution to remove lignin, wax and part of hemicellulose to obtain pretreated kapok fiber, soaking the pretreated kapok fiber in a 5% NaClO 2 The mixed solution of NaClO and citric acid was stirred for 3 to 4 hours to obtain activated kapok fibers. 2 The mass ratio with citric acid is 4:1;

[0027] S102, adding citric acid to the activated kapok fiber to adjust the pH value to 5.5-6.5, then adding 3-chloro-2-hydroxypropyltrialkylammonium chloride and acrylic acid, stirring and reacting at 60-80° C. for 80-120 minutes, and drying at 80° C. to obtain hydrophilic kapok fiber.

[0028] The plant fiber is a dried Chinese herbal medicine residue and a hydrophilic kapok fiber, the mass fraction of the hydrophilic kapok fiber is 10 to 20 parts, the dried Chinese herbal medicine residue is a dried second-level residue, which is a second-level residue obtained by low-temperature extraction of a mixture of ginger, angelica, atractylodes, poria and atractylodes. The mass fraction of the dried second-level residue is 80 to 100 parts; the mass ratio of 3-chloro-2-hydroxypropyltrialkylammonium chloride, acrylic acid and kapok fiber is 3 to 4: 1 to 2: 10 to 20.

[0029] S103, cutting the plant fiber into pieces with a high-speed shearing machine, surface treating the plant fiber with a 3% dilute sulfuric acid solution, then washing it with deionized water until it is neutral and placing it in a pulping machine for pulping to obtain plant fiber pulp; finally placing the plant fiber pulp in a high-pressure homogenizer for high-pressure homogenization to prepare a cellulose matrix solution.

[0030] S104, stirring to make the cellulose matrix solution evenly mixed and to expel the bubbles therein as much as possible, adjusting the viscosity to 20-50cp at a temperature of 50°C, coating it on a paper base, filtering the water to form a wet paper sheet, and finally placing the wet paper sheet in a flat plate dryer set at a temperature of 100°C to dry to a constant weight, thereby obtaining a ginger paper fiber matrix layer.

[0031] The ginger paper fiber matrix layer obtained in this way is dense, porous and highly hydrophilic.

[0032] Further, a ginger paper fiber energy storage layer loaded with polysaccharide nanoparticles is prepared, and the specific steps are as follows:

[0033] S201, cutting the plant fiber into pieces with a high-speed shearing machine, surface treating the plant fiber with a 3% dilute sulfuric acid solution, then washing it with deionized water until it is neutral and placing it in a pulping machine for pulping to obtain plant fiber pulp; finally placing the plant fiber pulp in a high-pressure homogenizer for high-pressure homogenization to prepare a cellulose carrier solution.

[0034] The plant fibers are dried Chinese herbal medicine residue and hydrophilic kapok fibers, the mass fraction of the hydrophilic kapok fibers is 60 to 70 parts, and the mass fraction of the dried Chinese herbal medicine residue is 20 to 30 parts;

[0035] The Chinese herbal medicine residue is a second-level residue obtained by low-temperature extraction of a mixture of ginger, angelica, atractylodes macrocephala, tuckahoe and atractylodes lancea.

[0036] S202, take natural mica powder and heat it to 500℃, keep it for 1 hour, obtain activated mica powder, dissolve the activated mica powder in 5mol / L nitric acid solution, stir it at 90℃ for 2-3 hours, filter it, wash it with 70℃ deionized water until it is neutral, evaporate it at 70℃, add cationic N,N-dimethylformamide, add deionized water, heat it to 80℃, react for 2-3 hours, centrifuge the solid, wash it with 70℃ deionized water, evaporate it at 70℃ and grind it to obtain modified nanoparticles with enlarged micropores and interlayer cations, which are recorded as cationic active carriers. Among them, the mass ratio of N,N-dimethylformamide to mica powder is 1:4-5.

[0037] S203, add cationic active carrier to the cellulose carrier solution, stir and disperse evenly at 60-70°C, adjust the pH value to 5.5-6.5, and discharge the bubbles as much as possible, adjust the viscosity to 20-50cp at 50°C, apply it to the paper base, filter the water to form a wet paper sheet, and finally place the wet paper sheet in a flat dryer set at 100°C to dry to constant weight to obtain a ginger paper fiber energy storage layer; at this time, the two-dimensional structure of mica and the hollow structure of kapok interact to form a two-dimensional network structure. Mica is used as a skeleton to connect into a porous and dense network structure.

[0038] Further, a large amount of polysaccharide nanoparticles with anions are prepared, specifically:

[0039] S204, dissolving the polysaccharide particles in deionized water, adjusting the pH value to 5.5-6.5, adding glutamic acid, stirring evenly, and obtaining a large amount of polysaccharide particle solution with anions. The ginger paper fiber energy storage layer is immersed in a large amount of polysaccharide particle solution with anions. The polysaccharide particles with anions are loaded into the micropores of the mica with cations under the action of electrostatic force to form a uniformly dispersed network structure, and finally placed in a flat dryer set at a temperature of 100°C for drying to constant weight, to obtain a ginger paper fiber energy storage layer loaded with polysaccharide nanoparticles.

[0040] The mass ratio of the cationic active carrier to the total mass of the plant fiber is 1:4-5; the mass ratio of glutamic acid to the polysaccharide particles is 1:8-10.

[0041] First, the physical electrostatic effect of glutamate is used to disperse the polysaccharide particles into tiny polysaccharide nanoparticles, which are then dispersed in the ginger paper energy storage layer. The cross-linking effect of mica is then used to stabilize the dispersion of the polysaccharide nanoparticles, forming a network structure loaded with polysaccharide nanoparticles.

[0042] After the kapok fiber is boiled in a 3% dilute sulfuric acid solution and then activated, the kapok fiber exhibits stronger hydrophilicity and has better reusability. The ginger paper fiber energy storage layer made of kapok fiber and mica nanoparticles has a higher porosity and uniform pore size of the nanofibers, which allows it to load more polysaccharide particles and has a higher drug loading capacity. At the same time, it promotes the drug-loaded film loaded with polysaccharide nanoparticles. The mesh structure of the mica polysaccharide nanoparticles in the ginger paper fiber energy storage layer stores energy, and under the drive of thermal energy, the polysaccharide nanoparticles in the drug-loaded film move toward the human body, thereby promoting the absorption of active ingredients by the human body and improving the overall ability of ginger paper to deliver drug efficacy.

[0043] Finally, a three-layer nanostructured ginger paper was obtained, with the outer layer being a 1-2 mm ginger paper fiber matrix layer, the middle layer being a 3-4 mm ginger paper fiber energy storage layer, and the inner layer being a 1-2 mm drug-loaded film loaded with polysaccharide nanoparticles.

[0044] The fiber energy storage layer prepared by modified mica particles and kapok nanofibers has good hydrophilicity and good mesh nanostructure, which can shorten the transmission path, so that the moisture in the body is absorbed by the kapok fibers, and the active substances are quickly transferred to the skin under the action of temperature difference through the mica network skeleton and absorbed by the human body. The drug-loaded film loaded with polysaccharide nanoparticles as a drug reservoir is conducive to the sustained release of drugs. Macromolecular drugs are generally difficult to pass through the cell membrane through osmosis due to their size limitations. The diameter of nanocarriers based on nanotechnology is usually 10 to 200nm, which is similar to the size of biological macromolecules such as proteins and nucleic acids, but at the same time it is much smaller than the size of cells and various organelles in cells. Therefore, it is easy to be absorbed by the human body and the drug effect can really play a role. In addition, mica particles have the function of energy storage, which can store a large amount of released capacity and release it slowly, which can also effectively avoid the energy being wasted in large quantities because it is not absorbed in time. The energy stored in the mica particles can be used when the energy is insufficient. With the promotion of the transfer of polysaccharide nanoparticles, it is more conducive to the uniform and continuous drug effect when the active ingredients are released.

[0045] Finally, a ginger paper loaded with polysaccharide nanoparticles is also provided. The ginger paper loaded with polysaccharide nanoparticles is a spacer used as a moxibustion spacer and has the function of transferring active ingredients.

[0046] The ginger paper fiber energy storage layer is loaded between the mica layers due to the effect of electrostatic attraction. When in the moxibustion state, the temperature of the surface layer in contact with moxibustion rises, and the mica particles and kapok fibers will expand. The active polysaccharide nanoparticles loaded between the layers will overcome the electrostatic attraction due to the violent Brownian motion and will be quickly transferred to the drug-loaded film layer loaded with polysaccharide nanoparticles through the mesh structure of the ginger paper fiber energy storage layer under the effect of the temperature difference. At the same time, the polysaccharide nanoparticles in the drug-loaded film layer are activated to be transferred to the surface layer close to the skin, to the human skin, and absorbed by the human body. At the same time, the moisture discharged by the human body is absorbed by the kapok fiber, which will further cause the kapok fiber and mica to absorb water and expand, and in turn act on the polysaccharide nanoparticles again, so that the micropores continue to expand, and the resistance of the polysaccharide nanoparticles to be further reduced, so as to quickly exert the drug effect. Moreover, as a network skeleton, the mica particles have the function of energy storage, and will absorb a large amount of energy and store it in the ginger paper fiber energy storage layer, which will also promote the movement of polysaccharide nanoparticles to intensify and promote the continuous and rapid transmission of active substances.

[0047] Compared with the prior art, the invention has the following beneficial effects:

[0048] 1) The present invention provides a method for preparing polysaccharide nanoparticles, wherein a mixture of various Chinese herbal medicines such as ginger, angelica, atractylodes, poria and atractylodes is subjected to a low-temperature extraction method to extract the active ingredient polysaccharide particles; a portion of the mixture is reacted with corn starch to form a drug-loaded film loaded with polysaccharide nanoparticles; a portion of the mixture is modified to obtain polysaccharide nanoparticles carrying a large amount of anions; and the filter residue of the Chinese herbal medicine and natural kapok fiber are used as a matrix, and the modified mica with enlarged micropores is used as a cation, and under the action of electrostatic force, the polysaccharide nanoparticles are directionally loaded on the ginger paper fiber energy storage layer with a mesh structure. The double-layer structure of the loaded polysaccharide nanoparticles significantly improves the ability of the ginger paper to load polysaccharide nanoparticles, and further protects the activity of the polysaccharide nanoparticles.

[0049] 2) The drug-loaded film loaded with polysaccharide nanoparticles uses gelatinized corn starch as a carrier, so that the polysaccharide nanoparticles are evenly dispersed in the film. The formed drug-loaded film has good adhesion and fits tightly to the skin. The formed film is soft and skin-friendly, feels comfortable and soft during use, and is suitable for all skin types of the human body.

[0050] 3) The present invention uses natural plant fiber paper as a matrix, and loads polysaccharide particles of active ingredients of various Chinese herbal medicines on this ginger paper matrix. The prepared ginger paper loaded with polysaccharide nanoparticles is a three-layer nanostructure, including a ginger paper fiber matrix layer, a ginger paper fiber energy storage layer and a drug-loaded membrane loaded with polysaccharide nanoparticles. The structure has the characteristics of good permeability, adsorption, adhesion, and drug-loaded conductivity, which helps the active ingredients loaded in the ginger paper to diffuse from the matrix to the dermis of the skin under the action of temperature difference, promotes the skin's absorption of the active ingredients, and truly solves the problem of the maximum degree of conduction of effective substances to the skin during moxibustion and being absorbed by the human body. It can also expel moisture and cold to the outside and transfer heat to the inside to transfer the active ingredients of Chinese medicine.

[0051] 3) The active ingredients of Chinese herbal medicine that can be carried on the ginger paper fiber sheet of the present invention have the advantages of strong drug carrying capacity, good flame retardancy and filtration, and outstanding energy-saving and environmental protection benefits. When moxibustion is in working state, the temperature control amplitude is 60-70°C, the sub-constant temperature retention rate is more than 95% within 5 hours, the skin burn rate is zero, and it is safe and reliable; this method uses the heat transfer technology principle in thermodynamics to effectively control the temperature of heat conduction of moxa stick combustion, thereby achieving a stable and long-term sub-constant temperature state. During the continuous process of moxibustion, since the surface temperature of the moxibustion suit is different from the body surface temperature of the moxibustion practitioner, the relative movement causes heat exchange. On the one hand, the moisture discharged by the human body can be absorbed and discharged by kapok, and on the other hand, the polysaccharide nanoparticle active substances in the ginger paper fiber energy storage layer can quickly transfer energy and active ingredients to the drug-loaded film through the microporous structure of mica, with the help of the mesh skeleton structure, and activate the active substances in the drug-loaded film layer to quickly free to the human skin and be absorbed by the human body, so that the drug effect can be maximized. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 , electron microscope image of the energy storage layer of ginger paper fiber. DETAILED DESCRIPTION

[0053] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content described in the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0054] Example 1

[0055] Polysaccharide nanoparticles are polysaccharide particles extracted from Chinese herbal medicine. First, the polysaccharide particles are extracted using a low-temperature extraction method, specifically:

[0056] 40 parts of ginger, 5 parts of angelica, 10 parts of atractylodes, 15 parts of poria and 5 parts of atractylodes are taken, cleaned, freeze-dried and then pulverized to obtain a pulverized mixture, a 70% ethanol solution of 4 times the weight of the pulverized mixture is added to the pulverized mixture, the mixture is placed in an ultrasonic extractor for extraction, and a first-stage extract and a first-stage filter residue are obtained by filtration for standby use; the first-stage extract is concentrated under reduced pressure to a concentrated solution of 0.1 times the weight of the first-stage extract to obtain a first concentrated solution;

[0057] Add 4 times 70% ethanol solution to the first-stage filter residue, place in an ultrasonic extractor for secondary extraction, filter to obtain a second-stage extract and a second-stage filter residue; reduce the pressure and concentrate the second-stage extract to a concentrated solution 0.1 times the weight of the second-stage extract; mix with the first concentrated solution to obtain a second concentrated solution, and fully stir at a temperature of 5°C;

[0058] The second concentrated solution was centrifuged and filtered, and concentrated under reduced pressure to remove ethanol to obtain an active substance extract. The Sevag method was used for deproteinization. Sevag reagent was added to the active substance extract at a volume ratio of 5:1, stirred for 60 minutes, and the upper polysaccharide solution was collected after standing for stratification. The organic layer and the protein layer were centrifuged, and the remaining polysaccharide solution was collected after centrifugation to obtain a deproteinized polysaccharide solution. The deproteinized polysaccharide solution was carefully transferred to a 3500Da dialysis bag for dialysis for 72 hours. After the dialysis was completed, it was concentrated under reduced pressure and freeze-dried to obtain polysaccharide particles. The second-stage filter residue was dried at low temperature for use;

[0059] Furthermore, the ginger paper loaded with polysaccharide nanoparticles is a three-layer nanostructure.

[0060] 5 parts of corn starch are gelatinized, cooled and mixed evenly with 1 part of polysaccharide particles, glycerol is added to the mixture and mixed evenly, then cast into a film, and dried to obtain a drug-loaded film loaded with polysaccharide nanoparticles;

[0061] Further, the ginger paper fiber matrix layer is prepared, specifically:

[0062] 20 parts of kapok fibers were boiled in 3% dilute sulfuric acid solution to obtain pretreated kapok fibers. The pretreated kapok fibers were soaked in 5% NaClO 2 solution and a mixed solution of citric acid for 4 hours to obtain activated kapok fibers;

[0063] The activated kapok fiber was added to a citric acid solution, the pH value was adjusted to 5.5, 3 parts of 3-chloro-2-hydroxypropyltrialkylammonium chloride and 2 parts of acrylic acid were added, the mixture was stirred at 80°C for 120 minutes, and the mixture was dried at 80°C to obtain the hydrophilic kapok fiber.

[0064] 20 parts of hydrophilic kapok fibers and 80 parts of dried Chinese herbal medicine residues were shredded with a high-speed shearing machine, the plant fibers were surface treated with a 3% dilute sulfuric acid solution, and then washed with deionized water until neutral and put into a pulping machine for pulping to obtain plant fiber pulp; finally, the plant fiber pulp was put into a high-pressure homogenizer for high-pressure homogenization to prepare a cellulose matrix solution;

[0065] The cellulose matrix solution was stirred to be uniformly mixed and the bubbles therein were discharged as much as possible, the viscosity was adjusted to 20cp at a temperature of 50°C, and the solution was coated on the paper base and filtered to form a wet paper sheet. Finally, the wet paper sheet was placed in a flat plate dryer set at a temperature of 100°C and dried to a constant weight to obtain a ginger paper fiber matrix layer;

[0066] Finally, the ginger paper fiber energy storage layer loaded with polysaccharide nanoparticles was prepared, and the specific steps were as follows:

[0067] 60 parts of hydrophilic kapok fiber and 20 parts of dried Chinese herbal medicine filter residue were cut into pieces by a high-speed shearing machine, and the plant fiber was surface treated with a 3% dilute sulfuric acid solution, and then washed with deionized water until neutral and put into a pulping machine for pulping treatment to obtain plant fiber pulp; finally, the plant fiber pulp was put into a high-pressure homogenizer for high-pressure homogenization treatment to prepare 100 parts of cellulose carrier solution. 20 parts of natural mica powder were heated to 500℃ and kept for 1 hour to obtain activated mica powder, which was dissolved in 5mol / L nitric acid solution, stirred at 90℃ for 3 hours, filtered, washed with 70℃ deionized water until neutral, and evaporated at 70℃, 5 parts of N,N-dimethylformamide were added thereto, and then deionized water was added, and the temperature was raised to 80℃. After reacting for 2 to 3 hours, the solid was centrifuged, washed with 70℃ deionized water, and evaporated and ground at 70℃ to obtain modified nanoparticles with micropore enlarged interlayer cations, which were recorded as cationic active carriers.

[0068] Add 20 parts of cationic active carrier to 100 parts of cellulose carrier solution, stir and disperse evenly at 70°C, adjust the pH value to 5.5, and discharge the bubbles as much as possible, adjust the viscosity to 30cp at 50°C, apply it to the paper base, filter the water to form a wet paper sheet, and finally place the wet paper sheet in a flat dryer set at 100°C to dry to constant weight to obtain a ginger paper fiber energy storage layer;

[0069] Dissolve 20 parts of polysaccharide particles in deionized water, adjust the pH value to 5.5, add 2 parts of glutamic acid, stir evenly, and obtain a large amount of polysaccharide particle solution with anions; soak the ginger paper fiber energy storage layer in a large amount of polysaccharide particle solution with anions for 2 hours, and finally place it in a flat dryer set at 100°C to dry to constant weight, and obtain a ginger paper fiber energy storage layer loaded with polysaccharide nanoparticles. Finally, the outer layer of the ginger paper loaded with polysaccharide nanoparticles is a 1mm ginger paper fiber matrix layer, the middle layer is a 3mm ginger paper fiber energy storage layer, and the inner surface layer is a 1mm drug-loaded film loaded with polysaccharide nanoparticles.

[0070] Example 2

[0071] Polysaccharide nanoparticles are polysaccharide particles extracted from Chinese herbal medicine. First, the polysaccharide particles are extracted using a low-temperature extraction method, specifically:

[0072] 30 parts of ginger, 8 parts of angelica, 15 parts of atractylodes, 10 parts of poria and 8 parts of atractylodes are taken, cleaned, freeze-dried and then pulverized to obtain a pulverized mixture, a 70% ethanol solution whose weight is 3 times of the pulverized mixture is added to the pulverized mixture, the mixture is placed in an ultrasonic extractor for extraction, and a first-stage extract and a first-stage filter residue are obtained by filtration for standby use; the first-stage extract is concentrated under reduced pressure to a concentrated solution whose weight is 0.2 times of the weight of the first-stage extract to obtain a first concentrated solution;

[0073] Add 3 times 70% ethanol solution to the first-stage filter residue, place in an ultrasonic extractor for secondary extraction, filter to obtain a second-stage extract and a second-stage filter residue; reduce the pressure and concentrate the second-stage extract to a concentrated solution 0.2 times the weight of the second-stage extract; mix with the first concentrated solution to obtain a second concentrated solution, and fully stir at a temperature of 5°C;

[0074] The second concentrated solution was centrifuged and filtered, and concentrated under reduced pressure to remove ethanol to obtain an active substance extract. The Sevag method was used for deproteinization. Sevag reagent was added to the active substance extract at a volume ratio of 5:1, stirred for 60 minutes, and the upper polysaccharide solution was collected after standing for stratification. The organic layer and the protein layer were centrifuged, and the remaining polysaccharide solution was collected after centrifugation to obtain a deproteinized polysaccharide solution. The deproteinized polysaccharide solution was carefully transferred to a 3500Da dialysis bag for dialysis for 72 hours. After the dialysis was completed, it was concentrated under reduced pressure and freeze-dried to obtain polysaccharide particles. The second-stage filter residue was dried at low temperature for use;

[0075] Furthermore, the preparation of ginger paper loaded with polysaccharide nanoparticles is a three-layer nanostructure. First, 5 parts of corn starch are gelatinized, cooled and mixed evenly with 1 part of polysaccharide particles, glycerol is added to the mixture and mixed evenly, and then cast into a film, and dried to obtain a drug-loaded film loaded with polysaccharide nanoparticles;

[0076] Further, the ginger paper fiber matrix layer is prepared, specifically:

[0077] 10 parts of kapok fibers were boiled in 3% dilute sulfuric acid solution to obtain pretreated kapok fibers. The pretreated kapok fibers were soaked in 5% NaClO 2 The activated kapok fiber was added to the citric acid solution, the pH value was adjusted to 6.0, and then 3 parts of 3-chloro-2-hydroxypropyltrialkylammonium chloride and 1 part of acrylic acid were added, stirred at 80°C for 80 minutes, and dried at 80°C to obtain the hydrophilic kapok fiber;

[0078] 10 parts of hydrophilic kapok fibers and 100 parts of dried Chinese herbal medicine residues were shredded by a high-speed shearing machine, the plant fibers were surface treated with a 3% dilute sulfuric acid solution, and then washed with deionized water until neutral and then put into a pulping machine for pulping to obtain plant fiber pulp; finally, the plant fiber pulp was put into a high-pressure homogenizer for high-pressure homogenization to prepare a cellulose matrix solution;

[0079] The cellulose matrix solution was stirred to be uniformly mixed and the bubbles therein were discharged as much as possible, the viscosity was adjusted to 30cp at a temperature of 50°C, and the solution was coated on the paper substrate and filtered to form a wet paper sheet. Finally, the wet paper sheet was placed in a flat plate dryer set at a temperature of 100°C and dried to a constant weight to obtain a ginger paper fiber matrix layer;

[0080] Finally, the ginger paper fiber energy storage layer loaded with polysaccharide nanoparticles was prepared, and the specific steps were as follows:

[0081] 70 parts of hydrophilic kapok fibers and 30 parts of dried Chinese herbal medicine residues were shredded by a high-speed shearing machine, the plant fibers were surface treated with a 3% dilute sulfuric acid solution, and then washed with deionized water until neutral and placed in a pulper for pulping to obtain plant fiber pulp; finally, the plant fiber pulp was placed in a high-pressure homogenizer for high-pressure homogenization to prepare 120 parts of a cellulose carrier solution.

[0082] Take 20 parts of natural mica powder and heat it to 500℃ for 1 hour to obtain activated mica powder. The activated mica powder is dissolved in 5 mol / L nitric acid solution, stirred at 90℃ for 2 hours, filtered, washed with 70℃ deionized water to neutrality, and evaporated at 70℃. 4 parts of cationic N,N-dimethylformamide are added thereto, and then deionized water is added. The temperature is raised to 80℃, and after reacting for 2 hours, the solid is centrifuged, washed with 70℃ deionized water, evaporated and ground at 70℃ to obtain modified nanoparticles with enlarged micropores and interlayer cations, which are recorded as cationic active carriers.

[0083] Add 20 parts of cationic active carrier to 120 parts of cellulose carrier solution, stir and disperse evenly at 60-70°C, adjust the pH value to 5.5-6.5, and discharge the bubbles as much as possible, adjust the viscosity to 40cp at 50°C, apply it to the paper base, filter the water to form a wet paper sheet, and finally place the wet paper sheet in a flat dryer set at 100°C to dry to constant weight to obtain a ginger paper fiber energy storage layer;

[0084] 18 parts of polysaccharide particles were dissolved in deionized water, the pH value was adjusted to 6.0, 2 parts of glutamic acid were added, and the mixture was stirred evenly to obtain a large amount of polysaccharide particle solution with anions; the ginger paper fiber energy storage layer was immersed in a large amount of polysaccharide particle solution with anions, and the polysaccharide particles with anions were finally placed in a flat dryer set at 100°C for drying to constant weight to obtain a ginger paper fiber energy storage layer loaded with polysaccharide nanoparticles. Finally, the outer surface layer of the ginger paper loaded with polysaccharide nanoparticles was a 2mm ginger paper fiber matrix layer, the middle layer was a 4mm ginger paper fiber energy storage layer, and the inner surface layer was a 1mm drug-loaded film loaded with polysaccharide nanoparticles.

[0085] Example 3

[0086] Polysaccharide nanoparticles are polysaccharide particles extracted from Chinese herbal medicine. First, the polysaccharide particles are extracted using a low-temperature extraction method, specifically:

[0087] 35 parts of ginger, 6 parts of angelica, 12 parts of atractylodes, 12 parts of poria and 6 parts of atractylodes are taken, cleaned, freeze-dried and then pulverized to obtain a pulverized mixture, a 70% ethanol solution of 4 times the weight of the pulverized mixture is added to the pulverized mixture, the mixture is placed in an ultrasonic extractor for extraction, and a first-stage extract and a first-stage filter residue are filtered for standby use; the first-stage extract is concentrated under reduced pressure to a concentrated solution of 0.1 times the weight of the first-stage extract to obtain a first concentrated solution;

[0088] Add 4 times 70% ethanol solution to the first-stage filter residue, place in an ultrasonic extractor for secondary extraction, filter to obtain a second-stage extract and a second-stage filter residue; concentrate the second-stage extract under reduced pressure to a concentrated solution 0.1 times the weight of the second-stage extract; mix with the first concentrated solution to obtain a second concentrated solution, and fully stir at 4°C;

[0089] The second concentrated solution was centrifuged and filtered, and concentrated under reduced pressure to remove ethanol to obtain an active substance extract. The Sevag method was used for deproteinization. Sevag reagent was added to the active substance extract at a volume ratio of 5:1, stirred for 50 minutes, and the upper polysaccharide solution was collected after standing for stratification. The organic layer and the protein layer were centrifuged, and the remaining polysaccharide solution was collected after centrifugation to obtain a deproteinized polysaccharide solution. The deproteinized polysaccharide solution was carefully transferred to a 3500Da dialysis bag for dialysis for 72 hours. After the dialysis was completed, it was concentrated under reduced pressure and freeze-dried to obtain polysaccharide particles. The second-stage filter residue was dried at low temperature for use;

[0090] Furthermore, the preparation of ginger paper loaded with polysaccharide nanoparticles is a three-layer nanostructure. First, 5 parts of corn starch are gelatinized, cooled and mixed evenly with 1 part of polysaccharide particles, glycerol is added to the mixture and mixed evenly, and then cast into a film, and dried to obtain a drug-loaded film loaded with polysaccharide nanoparticles;

[0091] Further, the ginger paper fiber matrix layer is prepared, specifically:

[0092] 15 parts of kapok fibers were boiled in 3% dilute sulfuric acid solution to remove lignin, wax and part of hemicellulose to obtain pretreated kapok fibers. The pretreated kapok fibers were soaked in 5% NaClO 2 The activated kapok fiber is added to the citric acid solution, the pH value is adjusted to 6.5, and then 3 parts of 3-chloro-2-hydroxypropyltrialkylammonium chloride and 1 part of acrylic acid are added, stirred at 80°C for 100 minutes, and dried at 80°C to obtain hydrophilic kapok fiber;

[0093] 15 parts of hydrophilic kapok fibers and 90 parts of dried Chinese herbal medicine residues were shredded with a high-speed shearing machine, the plant fibers were surface treated with a 3% dilute sulfuric acid solution, and then washed with deionized water until neutral and put into a pulping machine for pulping to obtain plant fiber pulp; finally, the plant fiber pulp was put into a high-pressure homogenizer for high-pressure homogenization to prepare a cellulose matrix solution;

[0094] The cellulose matrix solution was stirred to be uniformly mixed and the bubbles therein were discharged as much as possible, the viscosity was adjusted to 40cp at a temperature of 50°C, and the solution was coated on the paper substrate and filtered to form a wet paper sheet. Finally, the wet paper sheet was placed in a flat plate dryer set at a temperature of 100°C and dried to a constant weight to obtain a ginger paper fiber matrix layer;

[0095] Finally, the ginger paper fiber energy storage layer loaded with polysaccharide nanoparticles was prepared, and the specific steps were as follows:

[0096] 65 parts of hydrophilic kapok fibers and 25 parts of dried Chinese herbal medicine residues were shredded by a high-speed shearing machine, the plant fibers were surface treated with a 3% dilute sulfuric acid solution, and then washed with deionized water until neutral and placed in a pulper for pulping to obtain plant fiber pulp; finally, the plant fiber pulp was placed in a high-pressure homogenizer for high-pressure homogenization to prepare 110 parts of a cellulose carrier solution.

[0097] Take 20 parts of natural mica powder and heat it to 500°C for 1 hour to obtain activated mica powder. The activated mica powder is dissolved in 5 mol / L nitric acid solution, stirred at 90°C for 2 to 3 hours, filtered, washed with 70°C deionized water to neutrality, and evaporated at 70°C. 5 parts of cationic N,N-dimethylformamide are added thereto, and then deionized water is added, the temperature is raised to 80°C, and after reacting for 2 to 3 hours, the solid is centrifuged, washed with 70°C deionized water, evaporated and ground at 70°C to obtain modified nanoparticles with enlarged micropores and interlayer cations, which are recorded as cationic active carriers.

[0098] Add 20 parts of cationic active carrier to 110 parts of cellulose carrier solution, stir and disperse evenly at 70°C, adjust the pH value to 6.5, and make the bubbles therein discharged as much as possible, adjust the viscosity to 50cp at 50°C, apply it on the paper base, filter the water to form a wet paper sheet, and finally place the wet paper sheet in a flat plate dryer set at a temperature of 100°C to dry to constant weight, to obtain a ginger paper fiber energy storage layer;

[0099] Dissolve 15 parts of polysaccharide particles in deionized water, adjust the pH value to 5.5-6.5, add 1.5 parts of glutamic acid, stir evenly, and obtain a large amount of polysaccharide particle solution with anions; soak the ginger paper fiber energy storage layer in a large amount of polysaccharide particle solution with anions, and finally place it in a flat dryer set at 100°C to dry to constant weight, and obtain a ginger paper fiber energy storage layer loaded with polysaccharide nanoparticles. Finally, the outer layer of the ginger paper loaded with polysaccharide nanoparticles is a 1mm ginger paper fiber matrix layer, the middle layer is a 4mm ginger paper fiber energy storage layer, and the inner surface layer is a 1mm drug-loaded film loaded with polysaccharide nanoparticles.

[0100] Comparative Example 1, the hydrophilic kapok fiber is replaced by an equal amount of natural untreated kapok fiber, and the rest is the same as in Example 1;

[0101] Comparative Example 2, the cationic active carrier was replaced by an equal amount of natural mica powder, and the rest was the same as in Example 1; Comparative Example 3, the cationic active carrier was replaced by an equal amount of natural mica powder, the hydrophilic kapok fiber was replaced by an equal amount of natural untreated kapok fiber, and the rest was the same as in Example 1

[0102] Comparative Example 4: No three-layer nanostructure was prepared, and ginger slices with the thickness of ginger paper in Example 1 were directly used instead;

[0103] Comparative Example 5, using a Chinese patent with publication number CN109837787A, a kind of traditional Chinese medicine mugwort ginger paper and the ginger paper involved in Example 4 of its preparation process, with the same thickness as that in Example 1.

[0104] Experimental effect comparison data

[0105] 1. Morphological characterization of ginger paper

[0106] The morphology of the ginger paper fiber energy storage layer sample of Example 1 was observed using a field emission scanning electron microscope of FEI Nova NanoSEM450. The parameters of the scanning electron microscope were adjusted to set the acceleration voltage to 10 kV, the detection current to 10 mA, the resolution to 1.7 nm, and the magnification to 1000 times; the morphology is shown in Figure 1 .Depend on Figure 1 It can be seen that when the cationic active carrier loaded with polysaccharide nanoparticles is filled in the pores, a porous network skeleton is formed, and multiple micropores are evenly distributed with consistent pore sizes.

[0107] 2. Pore size analysis of ginger paper

[0108] The pore size of the ginger paper fiber energy storage layer of Examples 1-3 and Comparative Examples 1-3 was analyzed using a JW-BK200C specific surface area and pore size analyzer, as shown in Table 1; Table 1 shows that after Comparative Examples 1 and 3 used natural untreated kapok fibers that were not hydrophilically modified to make ginger paper fiber energy storage layers, the pore size of the fiber layer was too large. This is because the natural kapok fiber is hollow due to its own structure, and the hollow rate is as high as 80% to 90%. The fiber wall section presents micropores, and the contact angle with water is as high as 160°, which has very significant hydrophobic and lipophilic properties. Too loose structure and hydrophobic and lipophilic properties make the fiber pore size too large, which is not conducive to the loading and protection of polysaccharide nanoparticles, and it is easy to cause a large amount of active ingredients to be lost during storage. In Comparative Example 2, unmodified natural mica was used, which also made the pore size too large and the porosity too high. Therefore, the ginger paper fiber energy storage layer in Examples 1-3 uses modified kapok fiber as a matrix and a cationic active carrier, so that the two promote each other. The cationic active carrier forms a skeleton grid and is placed in the kapok fiber to form a dense, porous and uniformly pore-sized ginger paper fiber energy storage layer, which not only enables the cationic active carrier to be firmly attached to the plant fiber, but also enables the cationic active carrier to load polysaccharide nanoparticles to the maximum extent, thereby increasing the drug loading amount, and makes it difficult to be consumed during the storage process due to its dense structure.

[0109] Table 1 Pore size analysis data

[0110] Sample name Average pore size (nm) Porosity (%) Example 1 55.8 11.2 Example 2 57.2 12.5 Example 3 56.5 11.9 Comparative Example 1 398.7 24.2 Comparative Example 2 275.8 22.6 Comparative Example 3 519.6 21.3

[0111] 3. Determination of thermal conductivity of ginger paper

[0112] Ginger paper is used as a heat-insulating pad for moxibustion. The temperature of the ginger paper pad changes with time, and its thermal physical parameters are of great significance. Since moxibustion itself is a dynamic equilibrium system, it is affected by temperature and humidity. The ginger paper pad is porous to some extent, so it can be regarded as a porous medium. The size of the pores is a relative concept that has a significant impact on the heat transfer process of the porous medium. If the pores are filled with air, the thermal conductivity will be low, and when the pores are filled with liquid or solids with high thermal conductivity, the thermal conductivity will be large. The larger the thermal conductivity, the faster the heat transfer, the better the conductivity and drug transfer effect. The thermal conductivity of ginger paper after 1 hour of moxibustion of Example 1-3 and Comparative Example 1-5 using a YBF-3 thermal conductivity meter is shown in Table 2. As can be seen from Table 2, the thermal conductivity of each ginger paper layer in Example 1-3 is not much different, and the thermal conductivity is significantly improved than that of Comparative Example 1-5. This is because firstly, the ginger paper of Examples 1-3 contains activated mica and hydrophilic kapok fiber carriers. Mica absorbs the moisture generated during moxibustion and transfers nanoparticles, so that the pores are filled with liquid and solid. At the same time, the skeleton network structure of modified mica particles with high thermal conductivity is introduced in Examples 1-3, which has the function of energy storage. When filled in the pores of kapok fibers, the whole is connected into a large network system, which greatly improves the thermal conductivity system, thereby accelerating heat transfer. The electron microscope image of the ginger paper of Example 1 after treatment is shown in FIG. Figure 1 , it can be seen that when the activated mica loaded with polysaccharide nanoparticles is filled in the pores, a porous mesh skeleton is formed, forming a heat transfer mesh structure, which accelerates the spread of heat, and at the same time promotes the transmission of drug efficacy. Comparative Example 1 Because the ginger paper fiber uses natural kapok fiber, lipophilic type, and strong hydrophobicity, the ginger paper is filled with air, resulting in a very low thermal conductivity. Comparative Example 3 Because the ginger paper uses lipophilic natural kapok, and the unmodified mica powder is unevenly dispersed, the thermal conductivity of the ginger paper fibers in the surface and middle layers is very low. Comparative Example 4 is a natural plant fiber, so the thermal conductivity is also very low. Comparative Example 5 is a multi-layer Chinese medicine Aijiang paper, which is equivalent to a multi-layer plant fiber, so the thermal conductivity is also very low. Therefore, only the porous mesh skeleton structure of Example 1-3, using the activated mica, can also improve the thermal conductivity under the effect of large-scale energy storage, thereby accelerating the transmission of active ingredients.

[0113] Table 2 Thermal conductivity of ginger paper (W / m·K)

[0114]

[0115] Note: Comparative Example 4 is the thermal conductivity of ginger slices and Comparative Example 5 is the thermal conductivity of ginger paper layer.

[0116] 4. Particle size analysis of polysaccharide nanoparticles and cationic active carriers

[0117] The particle size of polysaccharide nanoparticles and cationic active carriers was analyzed using the OMCO NS-90Z PLus nanoparticle size and potential analyzer, and the particle size analysis and charge analysis were performed on the polysaccharide particles of Examples 1 to 3 and Comparative Examples 1 to 3. See Table 3

[0118] Table 3 Particle size analysis and charge analysis data

[0119]

[0120]

[0121] As can be seen from Table 3, the average particle size of the cationic active carrier prepared in Examples 1-3 is about 300nm, with a large amount of positive charge, while Comparative Examples 2-3 use natural mica powder, which has a large particle size and carries a small amount of negative charge, because the presence of electrostatic repulsion is not conducive to the loading of polysaccharide nanoparticles on mica particles. The average particle size of the polysaccharide particles prepared in Examples 1-3 and Comparative Examples 1-3 is relatively uniform, about 20nm, with a negative charge, and is easily loaded on a cationic active carrier with a large amount of positive charge. And when the Brownian motion of the 20nm polysaccharide nanoparticles is intense, they can break free from the electrostatic attraction, so that the polysaccharide nanoparticle active substances in the ginger paper fiber energy storage layer are quickly transferred to the human skin through the microporous structure of mica, with the help of the reticular skeleton structure, and are absorbed by the human body, so that the drug effect is maximized. .

[0122] The above description is only used to illustrate the technical solution of the present invention rather than to limit it. Any equal modifications and changes made to the technical solution of the present invention by ordinary persons in the art, as long as they do not deviate from the overall concept of the present invention, are still within the scope of the present invention.

Claims

1. A method for preparing ginger paper loaded with polysaccharide nanoparticles, characterized in that: The polysaccharide nanoparticles are polysaccharide particles extracted from Chinese herbal medicines. A low-temperature extraction method is provided, and the extraction method comprises the following steps: S001, clean the extract, freeze-dry it and then grind it to obtain a grinded mixture, S002, adding an ethanol solution 2 to 4 times the weight of the mixture to the crushed mixture, placing it in an ultrasonic extractor for extraction, filtering to obtain a first-stage extract and a first-stage filter residue for standby use; S003, concentrating the first-stage extract in step S002 under reduced pressure to a concentrated solution that is 0.1 to 0.2 times the weight of the first-stage extract to obtain a first concentrated solution; S004, adding 2 to 4 times ethanol solution to the first-stage filter residue in step S002, placing it in an ultrasonic extractor for secondary extraction, and filtering to obtain a second-stage extract and a second-stage filter residue; S005, concentrating the second-stage extract under reduced pressure to a concentrated solution 0.1 to 0.2 times the weight of the second-stage extract; mixing with the first concentrated solution in step S003 to obtain a second concentrated solution, and fully stirring at a temperature of 2° C. to 8° C.; S006, taking the second concentrated solution in step S005, performing centrifugal filtration, and concentrating under reduced pressure to remove ethanol, to obtain an active substance extract; the second filter residue is dried at low temperature and then used for later use; S007, deproteinization treatment was performed by Sevag method, Sevag reagent was added to the active substance extract at a volume ratio of 5:1, stirred for 30 to 60 minutes, and the upper polysaccharide solution was collected after standing and stratification, and the organic layer and the protein layer were centrifuged, and the remaining polysaccharide solution was collected after centrifugation to obtain a deproteinized polysaccharide solution, and the deproteinized polysaccharide solution was carefully transferred to a 3500Da dialysis bag for dialysis for 72 hours. After the dialysis, it was concentrated under reduced pressure and freeze-dried to obtain polysaccharide particles; S008, gelatinizing corn starch, mixing it evenly with polysaccharide particles after cooling, adding glycerol to the mixture and mixing evenly, casting it into a film, and drying it to obtain a drug-loaded film loaded with polysaccharide nanoparticles; the mass ratio of the polysaccharide particles to the corn starch is 1:

5.

2. The method for preparing ginger paper loaded with polysaccharide nanoparticles according to claim 1, characterized in that: The ginger paper loaded with polysaccharide nanoparticles is a three-layer nanostructure, which includes a ginger paper fiber matrix layer, a ginger paper fiber energy storage layer and a drug-loaded film loaded with polysaccharide nanoparticles from the outside to the inside. The preparation method of the ginger paper fiber matrix layer is specifically as follows: S101, boiling kapok fibers in a 3% dilute sulfuric acid solution to remove lignin, wax and part of hemicellulose to obtain pretreated kapok fibers, soaking the pretreated kapok fibers in a mixed solution of 5% NaClO2 solution and citric acid for 3 to 4 hours to obtain activated kapok fibers, wherein the mass ratio of NaClO2 to citric acid is 4:1; S102, adding citric acid to the activated kapok fiber to adjust the pH value to 5.5-6.5, then adding 3-chloro-2-hydroxypropyltrialkylammonium chloride and acrylic acid, stirring and reacting at 60-80° C. for 80-120 min, and drying at 80° C. to obtain hydrophilic kapok fiber; The plant fiber is a dried Chinese herbal medicine filter residue and a hydrophilic kapok fiber, the mass fraction of the hydrophilic kapok fiber is 10 to 20 parts, and the mass fraction of the dried Chinese herbal medicine filter residue is 80 to 100 parts; the mass ratio of 3-chloro-2-hydroxypropyltrialkylammonium chloride, acrylic acid and kapok fiber is 3 to 4: 1 to 2: 10 to 20; S103, chopping the plant fiber with a high-speed shearing machine, surface treating the plant fiber with a 3% dilute sulfuric acid solution, washing the plant fiber with deionized water until neutral, and then putting the plant fiber into a pulping machine for pulping to obtain plant fiber pulp; finally, putting the plant fiber pulp into a high-pressure homogenizer for high-pressure homogenization to prepare a cellulose matrix solution; S104, stirring to evenly mix the cellulose matrix solution and expel the bubbles therein as much as possible, adjusting the viscosity to 20-50 cp at 50° C., applying the solution to the paper base, filtering the water to form a wet paper sheet, and finally placing the wet paper sheet in a flat plate dryer set at 100° C. to dry the wet paper sheet to a constant weight, thereby obtaining a ginger paper fiber matrix layer; The preparation method of ginger paper fiber energy storage layer loaded with polysaccharide nanoparticles comprises the following specific steps: S201, chopping the plant fiber with a high-speed shearing machine, surface treating the plant fiber with a 3% dilute sulfuric acid solution, washing the plant fiber with deionized water until neutral, and then putting the plant fiber into a pulping machine for pulping to obtain plant fiber pulp; finally, putting the plant fiber pulp into a high-pressure homogenizer for high-pressure homogenization to prepare a cellulose carrier solution; The plant fibers are dried Chinese herbal medicine residue and hydrophilic kapok fibers, the mass fraction of the hydrophilic kapok fibers is 60 to 70 parts, and the mass fraction of the dried Chinese herbal medicine residue is 20 to 30 parts; S202, take natural mica powder and heat it to 500°C, keep it for 1 hour to obtain activated mica powder, dissolve the activated mica powder in 5 mol / L nitric acid solution, stir it at 90°C for 2-3 hours, filter it, wash it with 70°C deionized water until it is neutral, evaporate it at 70°C, add cationic N,N-dimethylformamide, add deionized water, heat it to 80°C, react for 2-3 hours, centrifuge the solid, wash it with 70°C deionized water, evaporate it at 70°C and grind it to obtain modified nanoparticles with enlarged micropores and interlayer cations, which are recorded as cationic active carriers; S203, adding a cationic active carrier to the cellulose carrier solution, stirring and dispersing the solution at 60-70°C, adjusting the pH value to 5.5-6.5, and allowing the bubbles therein to be discharged as much as possible, adjusting the viscosity to 20-50cp at 50°C, applying the solution to a paper substrate, filtering the solution to form a wet paper sheet, and finally placing the wet paper sheet in a flat dryer set at 100°C to dry the wet paper sheet to a constant weight, thereby obtaining a ginger paper fiber energy storage layer; S204, dissolving the polysaccharide particles in deionized water, adjusting the pH value to 5.5-6.5, adding glutamic acid, stirring evenly, and obtaining a large amount of polysaccharide particle solution with anions; soaking the ginger paper fiber energy storage layer in the large amount of polysaccharide particle solution with anions for 2-3 hours, and finally placing it in a flat dryer set at a temperature of 100°C to dry to constant weight, and obtaining a ginger paper fiber energy storage layer loaded with polysaccharide nanoparticles.

3. The method for preparing ginger paper loaded with polysaccharide nanoparticles according to claim 2, characterized in that: The mass ratio of N,N-dimethylformamide to mica powder is 1:4-5; the mass ratio of the cationic active carrier to the total mass of the plant fiber is 1:4-5; the mass ratio of the cationic active carrier to the polysaccharide particles is ≥1; and the mass ratio of glutamic acid to the polysaccharide particles is 1:8-10.

4. The method for preparing ginger paper loaded with polysaccharide nanoparticles according to claim 1, characterized in that: The Sevag reagent is a mixed solution of chloroform and n-butanol in a volume ratio of 4:1; the ultrasonic power is 50-100W, the extraction time is 1-2h, and the mass percentage concentration of the ethanol solution is 70-80%.

5. The method for preparing ginger paper loaded with polysaccharide nanoparticles according to claim 1, characterized in that: The extract is a Chinese herbal medicine mixture of ginger, angelica, atractylodes macrocephala, poria and atractylodes, wherein the ginger is 30-40 parts, the angelica is 5-8 parts, the atractylodes macrocephala is 10-15 parts, the poria is 10-15 parts and the atractylodes macrocephala is 5-8 parts.

6. The method for preparing ginger paper loaded with polysaccharide nanoparticles according to claim 2, characterized in that: The Chinese herbal medicine residue is the second-level residue obtained by low-temperature extraction of a mixture of ginger, angelica, atractylodes macrocephala, tuckahoe and atractylodes lancea.

7. The method for preparing ginger paper loaded with polysaccharide nanoparticles according to claim 1, characterized in that: The ginger paper loaded with polysaccharide nanoparticles is a three-layer nanostructured ginger paper, wherein the outer layer is a 1-2 mm ginger paper fiber matrix layer, the middle layer is a 3-4 mm ginger paper fiber energy storage layer, and the inner layer is a 1-2 mm drug-loaded film loaded with polysaccharide nanoparticles.

8. A ginger paper loaded with polysaccharide nanoparticles, wherein the ginger paper loaded with polysaccharide nanoparticles is prepared according to the preparation method of ginger paper loaded with polysaccharide nanoparticles according to any one of claims 1 to 7, and is a spacer gasket used as a moxibustion spacer, and has the function of transferring active ingredients.

Citation Information

Patent Citations

  • Traditional Chinese medicinal wormwood-ginger paper and preparation technology thereof

    CN109837787A

  • A method for preparing antibacterial paper loaded with nanoparticles

    CN113308001B

  • Chinese angelica acidic polysaccharide component, and preparation method and application thereof

    CN105985451A

  • Preparation method of nanoparticle-loaded antibacterial paper

    CN113308001A

  • Honeycomb-shaped biomass composite diaphragm for moxibustion partition and manufacturing process of honeycomb-shaped biomass composite diaphragm

    CN116637089A